Course Reinvention Guide through Realistic Mathematics Education to Improve Group Concept Understanding - Sunindri Sunindri; Sugiatno Sugiatno; Yulis Jamiah (JETL (Journal of Education, Teaching and Learning), 2018)
The preliminary study finds difficulty in group definition. Students have not had an understanding of the group definition concept. One alternative to give an understanding of the group definition concept is to develop reinvention guide to group definition. This research employs the realistic mathematics education learning approach to encourage and guide students to invent group definition concept. Therefore, this research aims at developing reinvention guide to group definition through realistic mathematics education to improve students understanding of group concept in FMIPA, UNTAN. The Research and Development (R & D) method is employed in guide development. The subjects are five six-semester students with formal experience in learning abstract algebra, particularly group theory, and students with average in group module test and lowest score in fifth pre-test. The data analysis results indicate that students’ group concept understanding is improved after receiving reinvention guide to group definition through realistic mathematics education based learning.